Sensing spaces, playing places. The sensuous geography of urban creativity - Petri, Jakub (Annales Universitatis Paedagogicae Cracoviensis. Studia de Arte et Educatione, 2022)
Urban creativity tends to be defined as a driving force of the ongoing changes in modern cities. While being a formally neutral term, the “creative,” in practice usually identifies all “good” sides of processes of urban transformations, especially those concerning the rise of spaces for sensual experiencing. The Creative City makes then a certain promise of aesthetic inclusion, enhanced participation, and autonomy for its citizens and visitors. However, the Creative City itself is neither an autonomous concept, nor the self-sufficient urban entity, but is entangled in economic, organizational, and social aspects of urban performance. All this makes us ask, is its promise trustworthy or rather empty?